Response spectrum method for building structures with general nonviscous damping models. (June 2022) - Xiao, Shiying; Wang, Mengfu
Abstract: Based on the free vibration solution of non-viscously damped linear systems obtained by Laplace transform, and using Duhamel's principle for dynamic analysis, a delicate and general solution of non-viscously damped linear multi-degree-of-freedom (MDOF) systems under seismic load, completely in real form, is presented. Response spectrum method and the corresponding modal combination rules are therewith extended to deal with general non-viscously damped structures. Finally, the accuracy and efficiency of proposed methods are discussed and compared with other developed methods by two numerical examples.